Assessing Oromotor Capacity in ALS: The Effect of a Fixed-Target Task on Lip Biomechanics - Eshghi, Marziye; Stipancic, Kaila L.; Mefferd, Antje; Rong, Panying; Berry, James D.; Yunusova, Yana; Green, Jordan R. (Frontiers in Neurology, 2019)
Alternating motion rate (AMR) is a standard measure often included in neurological examinations to assess orofacial neuromuscular integrity. AMR is typically derived from recordings of patients producing repetitions of a single syllable as fast and clear as possible on one breath. Because the task places high demands on oromotor performance, particularly articulatory speed, AMRs are widely considered to be tests of maximum performance and, therefore, likely to reveal underlying neurologic deficits. Despite decades of widespread use, biomechanical studies have shown that speakers often circumvent the presumed speed challenge of the standard AMR task. Specifically, speakers are likely to manipulate their displacements (movement amplitude) instead of speed because this strategy requires less motor effort. The current study examined the effectiveness of a novel fixed-target paradigm for minimizing the truncation of articulatory excursions and maximizing motor effort. We compared the standard AMR task to that of a fixed-target AMR task and focused specifically on the tasks’ potential to detect decrements in lip motor performance in persons with dysarthria due to amyotrophic lateral sclerosis (ALS). Our participants were 14 healthy controls and 17 individuals with ALS. For the standard AMR task, participants were instructed to produce the syllable /bɑ/ as quickly and accurately as possible on one breath. For the fixed-target AMR task, participants were given the same instructions, but were also required to strike a physical target placed under the jaw during the opening phase of each syllable. Lip kinematic data were obtained using 3D electromagnetic articulography. 16 kinematic features were extracted using an algorithmic approach. Findings revealed that compared to the standard task, the fixed-target AMR task placed increased motor demands on the oromotor system by eliciting larger excursions, faster speeds, and greater spatiotemporal variability. In addition, participants with ALS exhibited limited ability to adapt to the higher articulatory demands of the fixed-target task. Between the two AMR tasks, the maximum speed during the fixed-target task showed a moderate association with the ALSFRS-R bulbar subscore. Employment of both standard and fixed-target AMR tasks is, however, needed for comprehensive assessment of oromotor function and for elucidating profiles of task adaptation.